GLOBAL RISKS IN BRAND MANAGEMENT - Yudina, Nataliya (Current Problems of Sustainable Development, 2026)
The article demonstrates that in the context of polycrises arising from the multi-layered global instability and transformative crisis, brands become an attractive target for external influences, which poses risks to the brand management process itself. This issue requires a systematic approach to brand management processes within the context of a holistic view of the global economy. An analysis of the literature has shown that, despite their large number, these publications are fragmented, highly specialized, and focused on specific practical cases. Due to the lack of a unified holistic vision of the brand management process in a multi-layered era of global instability and transformative crisis it is difficult to understand global-level risks that are critical for brand management processes at the level of an individual enterprise. First, well-known global risks for the coming decade were analyzed. Since the pace of artificial intelligence development ranks second in terms of impact, a marketing study was conducted in which three different “transformer” GAI-chatbots served as respondents. The main research objective was to identify global risks for the coming decade that are underestimated by humanity. The responses received made it possible to identify global risks for brand management and determine relevant areas for further research.